KNOWLEDGE OF THE SOIL CHEMICAL COMPOSITION IN AREAS OF ECOLOGICAL SUCCESSION FOREST FIR (Abies guatemalensis REHDER) - José Vicente Martínez-Arévalo; Ovidio Aníbal Sacbaja-Galindo; José Pablo Prado-Córdova (Ra Ximhai, 2014)
The Chemical composition ( pH , elements major and minor , % S.B., CIC , % M.O. and N.T) on soils in open areas and forest fir (Abies guatemalensis Rehder ) in a successional gradient was studied. These results were related to vegetation through correlation analysis and Canonical Correspondence analysis. The aim was to show the relationships present between vegetation and soil chemistry through ecological succession in areas of cold climate. The results indicate that the vegetation is composed of 82 species of which 20 are the lower herbaceous layer, 34 the herbaceous layer of the upper, 21 shrubs and seven trees. The chemical characteristics of the soil through five successional stages have only few significant differences and not show a clear tendency to increase according to the degree of ecosystem development. A low percentage of correlations between vegetation and soil chemical characteristics are presented. The correspondence canonical analysis shows that the features that correlate with sites through vegetation are the K, and % S.B. and CIC. One can conclude that the approach of the study of the chemical composition of soils in areas of ecological sequence is complex, especially in high regions where, besides other factors, the temperature and humidity play an important role on the soil-vegetation dynamic.